Lisinopril alters contribution of nitric oxide and K(Ca) channels to vasodilatation in small mesenteric arteries of spontaneously hypertensive rats - Albarwani, S; Al-Siyabi, S; Al-Husseini, I; Al-Ismail, A; Al-Lawati, I; Al-Bahrani, I; Tanira, M O (Physiological research, 2015)
To investigate lisinopril effect on the contribution of nitric oxide (NO) and K(Ca) channels to acetylcholine (ACh)-induced relaxation in isolated mesenteric arteries of spontaneously hypertensive rats (SHRs). Third branch mesenteric arteries isolated from lisinopril treated SHR rats (20 mg/kg/day for ten weeks, SHR-T) or untreated (SHR-UT) or normotensive WKY rats were mounted on tension myograph and ACh concentration-response curves were obtained. Westernblotting of eNOS and K(Ca) channels was performed. ACh-induced relaxations were similar in all groups while L-NMMA and indomethacin caused significant rightward shift only in SHR-T group. Apamin and TRAM-34 (SK(Ca) and IK(Ca) channels blockers, respectively) significantly attenuated ACh-induced maximal relaxation by similar magnitude in vessels from all three groups. In the presence of L-NMMA, indomethacin, apamin and TRAM-34 further attenuated ACh-induced relaxation only in SHR-T. Furthermore, lisinopril treatment increased expression of eNOS, SK(Ca) and BK(Ca) proteins. Lisinopril treatment increased expression of eNOS, SK(Ca), BK(Ca) channel proteins and increased the contribution of NO to ACh-mediated relaxation. This increased role of NO was apparent only when EDHF component was blocked by inhibiting SK(Ca) and IK(Ca) channels. Such may suggest that in mesenteric arteries, non-EDHF component functions act as a reserve system to provide compensatory vasodilatation if (and when) hyperpolarization that is mediated by SK(Ca) and IK(Ca) channels is reduced.
Keywords: Dose-Response Relationship, Drug; Potassium Channel Blockers; vápníkem aktivované draslíkové kanály s vysokou vodivostí - alfa-podjednotky; zvířata; Male; Large-Conductance Calcium-Activated Potassium Channel alpha Subunits; Nitric Oxide Synthase Type III; Mesenteric Arteries; Lisinopril; signální transdukce; draslíkové kanály aktivované vápníkem; Vasodilation; Rats, Inbred SHR; arteriae mesentericae; lisinopril; Animals; Hypertension; mužské pohlaví; vazodilatancia; inhibitory ACE; potkani inbrední SHR; Vasodilator Agents; Intermediate-Conductance Calcium-Activated Potassium Channels; Potassium Channels, Calcium-Activated; Disease Models, Animal; Nitric Oxide; Antihypertensive Agents; vazodilatace; modely nemocí na zvířatech; potkani inbrední WKY; oxid dusnatý; nízkovodivostní draslíkové kanály aktivované vápníkem; antihypertenziva; Rats, Inbred WKY; Angiotensin-Converting Enzyme Inhibitors; vápníkem aktivované draslíkové kanály se střední vodivostí; blokátory draslíkových kanálů; synthasa oxidu dusnatého, typ III; hypertenze; Signal Transduction; vztah mezi dávkou a účinkem léčiva; Small-Conductance Calcium-Activated Potassium Channels